KEGAGALAN KEHAMILAN AKIBAT INFEKSI Toxoplasma gondiiGALUR RH DIPICU OLEH OVERPRODUKSI INTERFERON GAMMA (IFNγ γγ γ) - Sardjono, Teguh Wahju (Jurnal Kedokteran Brawijaya, 2005)
It has been already known that transplacental infiltration of parasites occurred during Toxoplasma infection in pregnancy; but pregnancy failures may due to some other previous mechanisms. Eighty BALB/c female mice were monogamously mated than devided into three pairs of study groupsand a pair of control group. On Day 9thpost mating, three pairs of study groups were intra-peritoneally infected by 10, 50 and 100 tachyzoites of RH strain Toxoplasma gondii, and the control groups were injected by PBS. Effect of treatment on the plasma level of IFNγ(ELISA) and number of litters were evaluated on the day 12thand day 15th-16th, represented second and third period of pregnancy.ANOVA and Path Analysis showed that duration of infection and the increase  of plasma IFNγ level decreased number of litters with coefficients of path of (-0,269; p=0,005) and (-0,377; p= 0,002) respectively. Decreasing number of litters was due toIFNγoverproduction, as response against RH strain of Toxoplasma gondii infection. This study showed that pregnancy failure in Toxoplasma infection is more due to indirect immuno-biochemical aspects rather than direct parasitological aspect. More studies to explain the basic molecular and immunological mechanisms of pregnancy failure in toxoplasmosis are still needed. Key words:Toxoplasmosis, IFNγ-overproduction, pregnancy failure